To Challenge the Republic: The French Army, de Gaulle and the Fourth Republic during the Algerian War, 1954-1962 - Whitehead, Robert W. (Tufts Archival Research Center, 2020)
This thesis deals with the collapse of the French Fourth Republic and the rise of the Fifth in the context of the Algerian War and collapsing civilian-military relations.